Drivers of Stock Market Returns in Sub-Saharan Africa: Evidence from Selected Countries - Tetteh, Joseph Emmanuel; Amoah, Anthony; Adenutsi, Deodat Emilson (Asian Development Policy Review, 2019)
This study investigates the drivers of stock market returns in selected Sub-Saharan African (SSA) economies. Secondary monthly data from January 2000 to December 2016 were collected and analyzed using the dynamic ordinary least square methods (DOLS) and fully modified ordinary least squares (FM-OLS) models to identify endogeneity and serial correlation and check for robustness. In accordance with a priori expectations, this study has proved the key driver of stock market returns across the selected countries is its lag. Although considerable literature exists on the principal determinants of stock market returns in SSA, there is an absence of empirical comparative studies of SSA countries that examine other salient internal and external variables. This study recommends that stockbrokers do not underestimate the importance of previous market performance, as it can potentially inform stock market predictions.